Resistance to monepantel in multiresistant gastrointestinal nematodes in sheep flocks in Rio Grande do Sul - Mallmann Júnior, Pedro Marino; Raimondo, Raquel Fraga e Silva; Rivero, Beatriz Riet Correa; Jacondino, Luiza Rodegheri; Gonçalves, Andressa Silveira; Silveira, Brenda Oliveira; Oberst, Eneder Rosana (Semina: Ciências Agrárias, 2018)
The excessive, indiscriminate, and continued use of anthelmintic drugs as control methods favors parasite resistance, and this phenomenon has been reported in Brazil and worldwide. The current status of parasite resistance to anthelmintic drugs in sheep flocks in Rio Grande do Sul was assessed by calculating the EPG count in the stool to estimate the prevalence of resistance to the anthelmintic drugs closantel, levamisole, fenbendazole, monepantel, and moxidectin in seven properties. The animals from each flock were randomly distributed in six groups according to the anthelminthic drug used, as follows: T1, levamisole; T2, fenbendazole; T3, monepantel; T4, moxidectin; T5, closantel; and T6, control. On day zero, fecal samples were collected, and each animal was treated with one anthelminthic drug. Fecal samples were collected again after 14 days to calculate the efficacy of each active principle. Coproculture was performed using a pool of fecal samples from each group on day 0 and 14 to identify the predominant genera and prevalence of helminths. The genera identified in the coprocultures were Haemonchus, Trichostrongylus, Oesophagostomum, and Teladorsagia. All flocks developed resistance to levamisole, fenbendazole, moxidectin, and closantel. Moreover, resistance to monepantel was found in four of the seven farms. These results demonstrate the critical situation of anthelmintic resistance in sheep flocks in Rio Grande do Sul and the need to adopt other integrated control measures in addition to anthelmintic treatment.